Avoiding Spinal Implant Failures in Osteoporotic Patients: A Narrative Review. Issue 1 (April 2023) - Schömig, Friederike; Becker, Luis; Schönnagel, Lukas; Völker, Anna; Disch, Alexander C.; Schnake, Klaus John; Pumberger, Matthias
Study design: Narrative review. Objectives: With an aging population, the prevalence of osteoporosis is continuously rising. As osseous integrity is crucial for bony fusion and implant stability, previous studies have shown osteoporosis to be associated with an increased risk for implant failure and higher reoperation rates after spine surgery. Thus, our review's purpose was to provide an update of evidence-based solutions in the surgical treatment of osteoporosis patients. Methods: We summarize the existing literature regarding changes associated with decreased bone mineral density (BMD) and resulting biomechanical implications for the spine as well as multidisciplinary treatment strategies to avoid implant failures in osteoporotic patients. Results: Osteoporosis is caused by an uncoupling of the bone remodeling cycle based on an unbalancing of bone resorption and formation and resulting reduced BMD. The reduction in trabecular structure, increased porosity of cancellous bone and decreased cross-linking between trabeculae cause a higher risk of complications after spinal implant-based surgeries. Thus, patients with osteoporosis require special planning considerations, including adequate preoperative evaluation and optimization. Surgical strategies aim towards maximizing screw pull-out strength, toggle resistance, as well as primary and secondary construct stability. Conclusions: As osteoporosis plays a crucial role in the fate of patients undergoing spine surgery, surgeons need to be aware of the specific implications of low BMD. While there still is no consensus on the best course of treatment, multidisciplinary preoperative assessment and adherence to specific surgical principles help reduce the rate of implant-related complications.